Late Quaternary environmental change in the Southern Cape, South Africa, from stable carbon and oxygen isotopes in faunal tooth enamel from Boomplaas Cave. (November 2016) - Sealy, Judith; Lee‐Thorp, Julia; Loftus, Emma; Faith, J. Tyler; Marean, Curtis W.
ABSTRACT: Pleistocene palaeoclimates and palaeoenvironments of southernmost Africa are important for understanding southern hemisphere climate dynamics and for reconstructing human evolution and early human settlement in this region. Measurements of δ 13 C in tooth enamel of 136 faunal specimens from the archaeological site of Boomplaas Cave, South Africa, show significant shifts in proportions of C3 and C4 vegetation from the earliest deposits, probably dating to Marine Isotope Stage (MIS) 5, to the late Holocene. Vegetation communities during the Last Glacial Maximum were strongly C3 ‐dominated, indicating an eastward expansion of the winter rainfall zone at this time. This is consistent with climate models postulating northwards shift and/or intensification of the circumpolar westerly frontal systems during glacials. Winter rainfall and lower temperatures, both of which favour C3 grasses, were clearly more important than lower p CO2 (which favours C4 grasses) in determining the nature of the vegetation. The intervals 40–36 and 17–14k cal a BP supported substantial quantities of C4 grasses, indicating a greater proportion of summer rainfall at these times. These two intervals correspond with warmer climates as reflected in Antarctic ice cores. δ 13 C of an as yet unnamed caprine indicate that these animals were primarily C3 grazers.